The Legal and Gender Education to Reduce Early Marriage Rates - Noor Lailatul Izza; Ida Musofiana (International Journal of Law Society Services, 2025)
Early marriage is a structural legal and social issue because it intersects with the protection of children's rights, gender equality, and the effectiveness of national marriage law. Although the state has set a minimum age for marriage through Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, the practice of child marriage persists due to strong cultural, economic, and patriarchal gender construction factors. This article aims to analyze the role of legal education and gender education in reducing the number of early marriages, as well as examine the importance of synergy between the state, universities, and the community through community service activities. This research uses a juridical-empirical method with a sociolegal approach, combined with community-based legal research. Data were obtained through normative studies of laws and regulations, as well as empirical data from legal counseling and gender education activities at the community level. The results show that legal education plays a strategic role in increasing public legal awareness and preventing the social legitimacy of early marriage, while gender education functions to deconstruct the patriarchal culture that places girls in a subordinate position. Furthermore, synergy between the state, universities, and the community has proven to be a key factor in building a sustainable, child-rights-focused legal culture. Therefore, community service-based legal and gender education needs to be positioned as a preventive and transformative instrument in efforts to prevent early marriage in Indonesia.